Design, analysis, and fabrication of walkgenerated bike / Muhammad Danish Iskandar Abd Rahman - Abd Rahman, Muhammad Danish Iskandar (2022)
This project is presenting an implement of green technology in transportation to prevent greenhouse gasses emission. The design of the walk generated-bike is made and selected for its capability and advantages. As fabrication start for the walk generated bike, it will be the proof for the concept of green technology in transportation. The use of treadmill in order to achieve the project objective as the power source will decrease greenhouse effect and provide a healthy lifestyle. As it is the first project it will targeting people under 90 kg. The rider will walk on the treadmill and the treadmill will drive the rear tire using by cycle chain. Thus, the objective of green technology in transportation will be achieve as there will be no greenhouse gasses emission. In advance, it will provide a healthier lifestyle to the user.